2014
DOI: 10.1111/febs.13097
|View full text |Cite
|
Sign up to set email alerts
|

Heparan sulfate in the regulation of neural differentiation and glioma development

Abstract: Heparan sulfate proteoglycans (HSPGs) are the main components of the extracellular matrix, where they interact with a large number of physiologically important macromolecules. The sulfation pattern of heparan sulfate (HS) chains determines the interaction potential of the proteoglycans. Enzymes of the biosynthetic and degradation pathways for HS chains are thus important regulators in processes ranging from embryonic development to tissue homeostasis, but also for tumor development. Formation of the nervous sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 140 publications
1
43
0
Order By: Relevance
“…In this study, we found that higher EMILIN3 expression was associated with worse OS and RFS in LGG patients and that promoter methylation in EMLIN3 was negatively correlated with gene expression. According to previous studies, the mechanism via which EMILIN3 affects glioma development may be explained by its interaction with heparin and heparin sulfate proteoglycans (HSPG) on the extracellular matrix [38-40]. Further studies are needed to explore the exact mechanisms of EMILIN3 in the tumor microenvironment and its pro-tumorigenic function in gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that higher EMILIN3 expression was associated with worse OS and RFS in LGG patients and that promoter methylation in EMLIN3 was negatively correlated with gene expression. According to previous studies, the mechanism via which EMILIN3 affects glioma development may be explained by its interaction with heparin and heparin sulfate proteoglycans (HSPG) on the extracellular matrix [38-40]. Further studies are needed to explore the exact mechanisms of EMILIN3 in the tumor microenvironment and its pro-tumorigenic function in gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…The biological function of hSulf-1 is to desulfate cell surface HSPG via the hydrolysis of 6-O-bond glucosamine sulfate in the highly sulfated sugar chains of HSPG [12]. Sulfation of HSPG is critical for interactions between extracellular growth factors and their receptor tyrosine kinases [13, 14]. Accordingly, desulfation of HSPG caused by hSulf-1 is capable of inhibiting the signaling pathways of various growth factors, including those of epidermal growth factor (EGF), fibroblast growth factor (FGF) and vascular endothelial growth factor (VEGF).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated regulatory effects of glycosaminoglycans on cell function including proliferation, differentiation and invasion [3,37,38]. In addition, several studies have examined the effects of specific HS and CS disaccharides on cell function.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%